2013
DOI: 10.2214/ajr.12.9641
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings in Eating Disorders

Abstract: After reviewing this article, the radiologist will understand the imaging findings in eating disorders. This knowledge will empower the radiologist to raise the question of a patient's eating disorder, a condition that may be unsuspected by the referring caregiver and could otherwise remain undiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…First, she had CKD and fluid management was more difficult than for patients without CKD. Second, it is said that substantial weight loss in AN is accompanied by atrophy of cardiac muscle, decreased cardiac mass, reduced ventricular wall thickness and cardiac chamber volumes [10][11][12], so CHF could readily and more seriously develop easily in the present case. Third, the physical damage or malinfluence by RTC, gastric bleeding and SAH can be critical on their own.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…First, she had CKD and fluid management was more difficult than for patients without CKD. Second, it is said that substantial weight loss in AN is accompanied by atrophy of cardiac muscle, decreased cardiac mass, reduced ventricular wall thickness and cardiac chamber volumes [10][11][12], so CHF could readily and more seriously develop easily in the present case. Third, the physical damage or malinfluence by RTC, gastric bleeding and SAH can be critical on their own.…”
mentioning
confidence: 81%
“…CKD is a great risk to induce cardiovascular diseases and easily trigger CHF. Persistent AN for a long period with serious malnutrition is also considered to damage myocardial cells [10][11][12]. Therefore, there is great possibility that serious RTC might occur in patients with AN and CKD if some other risk such as intracranial hemorrhage overlaps these diseases.…”
mentioning
confidence: 99%
“…Labial, buccal and palatal mucosa injuries, injuries to the tongue, periodontal disease, dental decay as well as non-carious lesions are observed [14][15][16]. These signs do not result from the disorder itself but mostly are the effect of various factors affecting the tissues, not always related to a given disease [17,18].…”
mentioning
confidence: 99%
“…[8][9][10] In general, the majority of the studies on AN have reported brain volume deficits and increased cerebrospinal fluid. 11,12 To our knowledge, no previous study has evaluated cerebral tissue abnormalities occurring in patients with anorexia neither during the disorder nor following treatment using MTI.…”
mentioning
confidence: 99%